Pemberdayaan Masyarakat Melalui Peningkatan Pemasaran Pada Usaha Kerupuk “Damai” Dusun Bonggan Kel. Blotongan Kota Salatiga - Pandi Afandi; Aan Istiyanto; Dina Ayu Lestari; Mada Adi Wibowo (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
SMEs or home traders are another term or term for productive economic businesses owned by individuals or business entities. MSMEs or home traders usually earn income that can be said to be the least compared to entrepreneurs in the medium and large categories. This is due to the small scope of sales and a lack of sales facilities and even the required capital. This implementation is supported by the Community Empowerment Practice Lecture (KPPM) organized by LP2M and STIE "AMA" Salatiga. On this occasion we will carry out a Community Empowerment Practical Lecture (KPPM) in Bonggan Hamlet, Blotongan Village in Salatiga City. Especially at one of the Home Traders who produces Rambak Crackers and Eggplant Crackers. This activity will take place from February 1, 2023 to February 23, 2023. The service activities are: a) Making product variations in terms of shape and taste and product packaging in the form of clip packaging. b) Install a business nameplate located in front of Mr. Ispan's house and c) Determine the location point via Google Maps, to help consumers find the cracker business.